المقاربة النصية في تنمية المهارات اللّغوية في التعليم الابتدائي بالجزائر - سحواج, امحمــد (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
The textual approach is a modern strategy in the field of language education, to provide the learner with language skills. And from it, the textual approach in language education takes the text as a pedagogical support to address all linguistic activities, which works to develop the language competencies and skills of the learner. Accordingly, in our research, we touched on the following points: 1) Textual Approach (Concepts), 2) Linguistic procedures for the textual approach, 3) Language book for the fifth year of primary education for the second generation. 4) The textual approach to the development of language skills through the Arabic language book for the fifth year of primary education, the second generation. تعدُّ المقاربة النّصية إستراتيجية حديثة في حقل تعليمية اللغة، لإكساب المتعلّم مهارات لغوية. ومنه فالمقاربة النّصية في تعليمية اللّغة، تتخذّ النّص كسند بيداغوجي لــمعالجة لمعالجة جميع الأنشطة اللّغوية، والذي يعمل على تنمية الكفاءات والمهارات اللغوية لدى المتعلم. وعليه تطرّقنا في مداخلتنا إلى النقاط التالية: (1) المقاربة النصّية (مفاهيم)، (2) الإجراءات اللّسانية للمقاربة النّصية، (3) كتاب اللغة للسنة الخامسة من التعليم الابتدائي للجيل الثاني، (4) المقاربة النصّية في تنمية المهارات اللّغوية من خلال كتاب اللّغة العربية للسنة الخامسة من التعليم الابتدائي الجيل الثاني.